Inter‐Aromatic Distances in Geobacter Sulfurreducens Pili Relevant to Biofilm Charge Transport. (21st January 2015) - Yan, Hengjing; Chuang, Chern; Zhugayevych, Andriy; Tretiak, Sergei; Dahlquist, Frederick W.; Bazan, Guillermo C.
Abstract : Geobacter sulfurreducens pili are implicated in facilitating electron transfer to electrode surfaces. Comparisons are made between the conductivity of pili and that of doped organic semiconductors, invoking mechanisms such as "electron hopping" or "metallic conduction". Analysis of inter‐aromatic distances in these pili models shows that charge‐carrier transport involving only the π ‐conjugated system of GS pili is negligible.